Financial Performance as a Mediation of Tax Avoidance Determinants in LQ45 Companies on the Indonesia Stock Exchange - Khairul Azwar; Elly Susanti; Supitriyani (Yayasan Ilomata, 2023)
Taxes are the main source of revenue in the State Budget (APBN) which accounted for 73% of all state revenue in 2019. Taxes have such an important role in sustaining the continuity of government and development. However, realized tax receipts never reached the target level between 2009 and 2020.This is because there are companies that carry out tax avoidance actions. The purpose of this study is to specifically analyze the variables that affect tax evasion in the LQ45 index companies of the Indonesian Stock Exchange. This research was conducted during the period 2017 –2022. The sampling technique used in this study is purposive sampling, in which criteria are determined based on the variables studied. The data analysis technique used is multiple simple linear regression analysis and a residual test for moderating variables. The F-test results show that institutional ownership, sales growth and Ln_total assets have a positive and insignificant effect on tax evasion. T-test results show that institutional ownership and sales growth have a negative and insignificant effect on tax evasion. However, Ln-Total_Asset has a negative and significant effect on tax evasion.